What are the internal determinants of return on assets and equity of the energy sector in Turkey? - Bilgehan Tekin (Financial Internet Quarterly, 2022)
The rapid transformations and developments experienced today have increased the importance of energy resources and sustainable energy. In this context, the success and profitability of the activities of companies engaged in energy production and distribution is an important topic. This study, which was carried out in such an environment, was aimed to determine the financial indicators that statistically significantly affect the return on assets (ROA) and equity (ROE) of companies that produce and distribute oil, gas and electricity in Turkey. In the context of the energy sector, ROA and ROE increase competitiveness and provide companies with an advantage in terms of financial success and sustainability of operations. Considering the increasing importance of energy, it is important to determine the internal factors that have an impact on the profitability of energy companies. The research was carried out on a sample of 16 companies operating in the Turkish energy sector and traded on Borsa Istanbul. A panel linear regression model was used to identify the strongest predictors of ROA and ROE. The study used fifteen ratios that are believed to impact ROA and ROE significantly. According to the results obtained, ROE is influenced by CSR (at the significance level of 10%), QR, LR, RTO, ITR, and TA, and ROA is influenced by RTO, CSR, LR, QR (10%), and PB.
Keywords: G12; G39; C23; 330; energy sector; ROA; ROE